1997
DOI: 10.1074/jbc.272.43.26822
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of a Specific Metal Ion in the Transition of the Hammerhead Ribozyme to Its Catalytic Conformation

Abstract: Previous crystallographic and biochemical studies of the hammerhead ribozyme suggest that a metal ion is ligated by the pro-R p oxygen of phosphate 9 and by N 7 of G10.1 and has a functional role in the cleavage reaction. We have tested this model by examining the cleavage properties of a hammerhead containing a unique phosphorothioate at position 9. The R p -, but not S p -, phosphorothioate reduces the cleavage rate by 10 3 -fold, and the rate can be fully restored by addition of low concentrations of Cd 2؉,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
100
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 26 publications
15
100
1
Order By: Relevance
“…In this study, phosphorothioate substitution at P9 inhibited cleavage, a result that suggested the importance of the P9 oxygen as a metalbinding site. This suggestion was later supported by Peracchi et al in a study that involved the speci®c stereoselective introduction of a phosphorothioate moiety at the P9 position (Peracchi et al 1997). An Rp-but not a Sp-phosphorothioate reduced the cleavage rate 1000-fold, but the original rate was restored by the subsequent addition of a low concentration of Cd 2 ions, which are thiophilic.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…In this study, phosphorothioate substitution at P9 inhibited cleavage, a result that suggested the importance of the P9 oxygen as a metalbinding site. This suggestion was later supported by Peracchi et al in a study that involved the speci®c stereoselective introduction of a phosphorothioate moiety at the P9 position (Peracchi et al 1997). An Rp-but not a Sp-phosphorothioate reduced the cleavage rate 1000-fold, but the original rate was restored by the subsequent addition of a low concentration of Cd 2 ions, which are thiophilic.…”
Section: Discussionmentioning
confidence: 81%
“…By contrast, and in agreement with previous ®ndings (Ruffner et al 1990;Tuschl & Eckstein 1993;Peracchi et al 1996), k cat was reduced signi®cantly by the replacement of G 10.1 with 7-deazaguanine; the k cat of 0.0064 min À1 for 7-deaza-R34 was considerably lower than that of 0.19 min À1 for R34. However, the extent of the reduction (30-fold) caused by the removal of N7 of G 10.1 was much smaller than that (1000-fold reduction) caused by the introduction of the Rp-phosphorothioate at the P9 position (Peracchi et al 1997). This result suggests that, even though binding of Mg 2 to N7 of G 10.1 is catalytically important (Peracchi et al 1998;Wang et al 1999), it is not absolutely indispensable.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Oligonucleotides were made by solid phase synthesis and supplied by the Protein and Nucleic Acid Facility at Stanford University or were gifts from L. Beigelman (Ribozyme Pharmaceuticals Inc.). Oligonucleotide substrates (Chart 1) were 5′-end-labeled using [γ- 32 P]ATP and T4 polynucleotide kinase and purified by electrophoresis on 24% nondenaturing polyacrylamide gels, as described previously (36,37). Oligonucleotides for inhibition studies were purified by ionexchange HPLC.…”
Section: Methodsmentioning
confidence: 99%
“…Specific metal ion ligands have been identified by metal ion specificity switch experiments (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). These experiments exploit the preference of nitrogen and sulfur ligands to interact more strongly with soft metal ions, such as Mn 2+ , than with hard metal ions, such as Mg 2+ .…”
mentioning
confidence: 99%